Initial national investigation of the prenatal diagnosis of congenital heart malformations in Japan-Regional Detection Rate and Emergency Transfer from 2013 to 2017. Issue 6 (December 2021) - Matsui, Hikoro; Hirata, Yasutaka; Inuzuka, Ryo; Hayashi, Taiyu; Nagamine, Hiroki; Ueda, Tomomi; Nakayama, Toshio
Highlights: This is the first national survey of fetal detection for congenital heart diseases (CHDs) in Japan Overall prenatal detection rate is low in Japan compared to the European countries Significant regional gaps of detection rates are recognized in Japan Fetal diagnosis significantly reduces risks of emergency transfer for CHDs Periodic official surveillance for prenatal cardiac diagnosis is required Abstract: Background: Investigation into the detection rate (DR) of congenital heart diseases (CHDs) in fetuses is important for the assessment of fetal cardiac screening systems. Objectives: We highlight issues of fetal cardiac screening in Japan. Methods: We performed an initial national survey of fetal diagnosis of CHDs from the data of the national registry for congenital heart surgery from 2013 to 2017. Subjects were neonates and infants with moderate or severe CHDs. We investigated DR in each prefecture in Japan and emergency transfer (ET) for neonates by analyzing distance and admission day of ET with or without fetal diagnoses. Results: : The overall average DR in Japan was 0.41 (0.02 increase every year). No regional significant relationship was found between DR and population in each prefecture. ET was performed in 12% of neonates with prenatal diagnosis and in 63% of neonates without resulting in significant risk for ET in fetuses without a fetal diagnosis [OR 13.3 (11.6−15.3), p<0.001]. The distance of ET was shorter and admission was earlier in the neonates with a prenatal diagnosis than in those without [median 6.6 km (IQR: 4.1-25.7) vs 17.0 km (IQR: 7.4-35.3), median 0.0 day (IQR: 0.0-0.0) vs 0.0 day (IQR: 0.0-1.0), p<0.001, p<0.001, respectively] Conclusions: Prenatal cardiac diagnosis reduces geographic and chronological risks of ET for moderate to severe CHDs. DR is still developing and periodic official surveillance is required for improving prenatal cardiac diagnosis in Japan. Graphical abstract: Image, graphical abstract